Determining the Validation of Homegrown Stethoscope Simulator for Cardiopulmonary Training - Fadelelmoula, Tarig Eltoum Yagoub (Highlights on Medicine and Medical Research Vol. 13, 2021)
Background: Public protection is greatly enhanced by the knowledge of health care practitioners. Advocates of simulation-based curriculum assert that this modality plays an especially significant role. Auscultation with stethoscope is an indispensable tool for optimal management of cardiopulmonary patients. However, the acquisition of sufficient training in cardiopulmonary auscultation is not straightforward because of the technical and ethical problems. Aims: The aim of this study is to validate a homegrown stethoscope simulator for cardiopulmonary auscultation developed by the author and claimed to be of a low-cost and high-fidelity. Materials and Methods: The hardware was built from a normal clinical stethoscope and a bluetooth headset, and the software is a single PowerPoint presentation slide with links to cardiopulmonary sounds’ audio tracts. The stethoscope simulator was verified by the inventor, and a panel of experts was asked to evaluate its value as a training tool, relevance to practice, physical attributes, realism of experience, ability to perform tasks, realism of material” and realism of auscultation sounds. The validity of this homegrown stethoscope simulator was assessed by a panel of experts. The members had a session on the simulator and how it works, allowed to physically examine the stethoscope simulator, instructed on how to use it, and then auscultated all its cardiopulmonary sounds. A survey was provided to each member of the panel, and they were asked to rate their responses using a 5-point Likert scale as follows: strongly disagree (1), disagree (2), neutral (3), agree (4), and strongly agree (5). Results: Experts in cardiology, respiratory medicine and respiratory care agreed upon the characteristics and attributes of this stethoscope simulator and the observed average of the “global assessment” of the stethoscope simulator was acceptable. The cost of fabrication of one simulator of this type was approximately 100 USD. Conclusion: Primary evidence shows that this homegrown stethoscope simulator is a valuable instrument that can be built into bedside training and clinical experience labs to help undergraduate students understand and teach cardiopulmonary auscultation.